Effect Of Use Of The Focusky Application On Results Learning Arts And Culture For Class X Students Madrasah Aliyah Ddi Kulo - Aini, Aini; M, Usman; B, Hasanuddin; Hermansyah, Sam (International Journal of Language and Ubiquitous Learning, 2023)
Background. Researchers will examine the impact of the Focusky app on Arts and Culture learning for 10th-grade students at Madrasah Aliyah DDI Kulo. Pre-observation reveals conventional teaching methods in use. The introduction of Focusky is expected to enhance learning, offering a dynamic experience for both students and teachers.Top of Form. Purpose.This study on the use of the Focusky application in Arts and Culture education for 10th-grade students at Madrasah Aliyah DDI Kulo is expected to contribute significantly. Findings may enhance teaching methods, particularly in the Arts, improving overall learning quality and simplifying the educational process. Method.This use method approach quantitative. According to Sugiyono (2017) study quantitative is "Method study Which based on the philosophy of positivism . Used to research populations or sample certain, collection data use instruments study, analysis data nature quantitative or statistics, with objective For test hypothesis Which has set. Results.This research was carried out with the aim of finding out    whether there was an effect of using Focusky on the Arts and Culture learning outcomes of class X Madrasah Aliyah DDI Kulo students by   taking a sample of 26 class X Madrasah Aliyah DDI Kulo students. In determining the experimental and control group students used a totally  sampling technique system. Conclusion.Based on the results of this research, several conclusions can be drawn as follows: The use of Focusky in the learning process has an influence on the Arts and Culture learning outcomes of class X Madrasah Aliyah DDI Kulo students. This is because by using Focusky teachers and students can carry out the teaching and learning process more easily and convey information to students well and interestingly.